Protection of State Border in Caucasus at End of 19th Century: Karsk Border Brigade - K, A. Pavlov; O. B. Klochkov (Научный диалог)
The process of formation and development of the protection of the state border in the Caucasus at the end of the 19th century (using the example of the Karsk border brigade) is analyzed in the article. The relevance of the study is due to the fact that in historical research insufficient attention is paid to the protection of the state border in the Caucasus by border guard units at the end of the 19th century. It is shown that under the conditions of the introduction of protective customs duties, as a result of which smuggling activities began to develop actively, without specialized units, the Russian Empire was unable to protect its economic interests in the border space in the Caucasus. It is noted that the development of the state border guard system was carried out in a tense, unstable military-political situation, accompanied by constant armed clashes with bandit formations. It is indicated that in these conditions, the protection of the state border was carried out by the border guards together with military units, which in turn negatively affected the quality of the protection of the economic interests of the Russian Empire in the region. It is concluded that the development of the system for protecting the state border in the Caucasus was a consequence of the existing threats to national security in the region.